2019
DOI: 10.1038/s41419-019-1743-6
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of HDAC4 by PP2A-Bδ unravels a new role for the HDAC4/MEF2 axis in myoblast fusion

Abstract: Muscle formation is controlled by a number of key myogenic transcriptional regulators that govern stage-specific gene expression programs and act as terminal effectors of intracellular signaling pathways. To date, the role of phosphatases in the signaling cascades instructing muscle development remains poorly understood. Here, we show that a specific PP2A-B55δ holoenzyme is necessary for skeletal myogenesis. The primary role of PP2A-B55δ is to dephosphorylate histone deacetylase 4 (HDAC4) following myocyte dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Of interest, HDAC4 protein is more abundant in the slow SL muscle, although the basis of this discrepancy is not known yet [27]. The main role of HDAC4 in myogenesis has been extensively studied and is through direct repression of MEF2, the master regulator of slow fiber program [4, [28][29][30][31]. In addition, HDAC4 expression is upregulated upon muscle injury and it is essential for an appropriate muscle regeneration [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, HDAC4 protein is more abundant in the slow SL muscle, although the basis of this discrepancy is not known yet [27]. The main role of HDAC4 in myogenesis has been extensively studied and is through direct repression of MEF2, the master regulator of slow fiber program [4, [28][29][30][31]. In addition, HDAC4 expression is upregulated upon muscle injury and it is essential for an appropriate muscle regeneration [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In muscle cells, we succeeded in identifying HDAC4 as the specific substrate of PP2A holoenzymes containing the Bδ regulatory subunit. Interestingly, other class IIa HDACs were not regulated by PP2A-Bδ [4].…”
Section: Mef2 Also Controls Myocyte Fusionmentioning
confidence: 95%
“…The original goal of our study was to investigate the role of protein phosphatases during myogenesis [4]. Because protein kinases have long been known to be crucial in this process, the involvement of their counterpart, protein phosphatases would also be expected.…”
Section: Mef2 Also Controls Myocyte Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we demonstrate that Sorbs1 acts upstream of RhoGTPases to control EC actomyosin cytoskeleton and migratory behavior. Prior to this work, only few studies had alluded to potential connections between SoHo proteins and RhoGTPases signaling50,51,77,78 . Although extension of filopodia and migration of leading ECs during BMP-induced CVP morphogenesis was shown to be dependent on the Cdc42 RhoGTPase71 , we found that Cdc42 activity was not affected in the absence of Sorbs1 in ECs.…”
mentioning
confidence: 99%